The impact of knowledge management strategies on quality of educational service Study analytical for the opinions of a sample of workers in public and private universities - Lama Qais Raouf Al-Zubaidi; Dr. Abdul Nasser Alk Hafiz (Zien Journals, 2022)
The current research seeks to identify the impact of knowledge management strategies as an independent variable across its dimensions (coding strategy, personalization strategy) on quality of educational services a variable a follower across its dimensions (academic aspects, content continuous improvement, academic experience, academic advising, student resources and services), In public and private universities, the results were reached using the statistical program such as (SPSS.V.25) and the program (Amos.V.25).To analyze the data to reach conclusions, the most prominent of which was the existence of a correlation and impact relationship between knowledge management strategies and the quality of educational service, and based on the conclusions reached.
Keywords: knowledge management strategies; Quality of educational service; quality; existence